U.S. farmers market attendance and experiences - Laura Witzling; Bret Shaw; Darlene Wolnik (Journal of Agriculture, Food Systems, and Community Development)
To provide farmers market leaders and researchers with new insights about farmers market attendees, given shifting consumer preferences and demographics, we conducted a nearly nationally representative survey in the United States. Among the 5,141 respondents, 38.51% reported attending farmers markets infrequently (i.e., five or fewer times per year), and 41.78% reported attending with more regularity (i.e., six or greater times per year). In combination, this equated to 80.30% of the entire sample having at least some experience with farmers markets (i.e., attending once per year or more). Of note, farmers markets were defined as places to buy local food directly from more than one vendor. Top motivations for attending included getting fresh food, supporting local farmers, getting high-quality food, and doing something fun, suggesting that promoting farmers markets with those themes should resonate with audiences. The top challenge to attendance was forgetting about farmers markets, indicating that campaigns or strategies to remind individuals about markets could be beneficial. Additionally, the majority of attendees reported that they ate healthier because of farmers markets and that they did nonconsumer activities at farmers markets, such as socializing and learning, underscoring that farmers markets can be a shared community experience that goes beyond consumption. We recommend that future work build on our results to further investigate how to expand the customer base for farmers markets and help people access the many benefits they provide.